Conditionality Revisited : A New Approach in Burkina Faso - Emblad, Stefan; Hervio, Gilles; Humphreys, Chuck (World Bank, Washington, DC, 2012)
Donors have typically linked quick-disbursing assistance programs to conditions related to policy reforms. But there is growing frustration with how conditionality has worked in practice. Research has shown that traditional conditionality usually does not "buy" reforms. Moreover, because aid funds are fungible within government budgets, a results-based approach is needed to enhance aid effectiveness. At the initiative of the European Commission, the Strategic Partnership with Africa is piloting a new approach to conditionality in Burkina Faso to explore changes that enhance donor coordination, foster country ownership of reforms, and smooth aid flows--and so increase aid effectiveness. A driving feature of the approach is a focus on the outcomes of government reforms and policies.